2016
DOI: 10.1371/journal.pone.0154989
|View full text |Cite
|
Sign up to set email alerts
|

Why p-OMe- and p-Cl-β-Methylphenethylamines Display Distinct Activities upon MAO-B Binding

Abstract: Despite their structural and chemical commonalities, p-chloro-β-methylphenethylamine and p-methoxy-β-methylphenethylamine display distinct inhibitory and substrate activities upon MAO-B binding. Density Functional Theory (DFT) quantum chemical calculations reveal that β-methylation and para-substitution underpin the observed activities sustained by calculated transition state energy barriers, attained conformations and key differences in their interactions in the enzyme’s substrate binding site. Although both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…[141] The applications among the other studies are mainly in the validation domain for conserved water molecules in crystal structures. [142][143][144] WaterDock has been incorporated into another solvation program, Dowser++, to accurately predict water at protein interiors. [145] The latter is a development of the Dowser software, [146] performing the calculation on the whole protein space followed by further analysis.…”
Section: In Silico Methods Predicting Water Positionsmentioning
confidence: 99%
“…[141] The applications among the other studies are mainly in the validation domain for conserved water molecules in crystal structures. [142][143][144] WaterDock has been incorporated into another solvation program, Dowser++, to accurately predict water at protein interiors. [145] The latter is a development of the Dowser software, [146] performing the calculation on the whole protein space followed by further analysis.…”
Section: In Silico Methods Predicting Water Positionsmentioning
confidence: 99%
“…Fierro et al have reported variation in the biological activity displayed by a couple of p ‐methoxy‐β‐methylphenethylamine ( p ‐MMP), where the inhibitor p ‐chloro‐β‐methylphenethylamine ( p ‐CMP) becomes a substrate when a methoxy group replaces its p ‐chloro substituent. Despite their structural and chemical commonalities, p ‐CMP and p ‐MMP displayed distinct inhibitory and substrate activities upon MAO‐B binding.…”
Section: Molecular Modeling Studies On Mao‐b and Its Inhibitorsmentioning
confidence: 99%
“…In addition to MAO enzymes, an EVB study supported by DFT cluster calculations suggests that the hydride transfer mechanism is involved in the function of the DAO enzyme [44]. Apart from EVB methodology, reactions catalyzed by MAO enzymes have been studied by the "traditional" QM/MM approach including DFT methodology in the quantum part [45], or by cluster models treated by DFT [37,46,47]. Furthermore, through a variety of simulation methods, we addressed the mechanism of irreversible inhibition of MAO-B by selegiline and rasagiline, together with their binding into the enzyme's active site [48], but also focusing on the rate-limiting step by the EVB approach [49].…”
Section: Introductionmentioning
confidence: 99%